Classical Learning Analysis Pondok Modern Darussalam Gontor in Improving Superior School Management - Faizal Alif Hidayat; Nurdyansyah Nurdyansyah; Siti Ruchana (Proceedings of The ICECRS, 2020)
Education as a level of quality of human life both outwardly and mathematically, individually or socially in accordance with the foundation on a well-planned system so that it is followed by the application of an appropriate and correct curriculum. The desired educational goals are in accordance with the development of zaan. Therefore the success or failure of education depends on the curriculum used, although it is not very important on other aspects of education.The role of curriculum courses in the education system is very important, then educational institutions must be able to implement a curriculum that is able to bring the actual educational conditions in forming intellectually, skillful and morally capable individuals who are able to demonstrate their existence as an educational institution that survives in any zama development that does not must release its original identity as an educational institution that consistently maintains old traditions.